HUBUNGAN ANTARA FAKTOR PENGETAHUAN ISTRI DAN DUKUNGAN SUAMI TERHADAP KEJADIAN UNMET NEED KB PADA PASANGAN USIA SUBUR DI KELURAHAN SIANTAN TENGAH KECAMATAN PONTIANAK UTARA TAHUN 2014 - ., Risnawati Wahab (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Unmet need for family planning is reproductive couple whowant to delay pregnancy or do not want to have more children, but do notusing any method of contraception. Among subdistricts in pontianak citythe highest prevalence of unmet need for family planning is found in NorthPontianak (18,97%). The highest number of reproductive couple is foundin Central Siantan (6326 couples). Wife’s knowledge and husband’ssupport are suggested to influence the incindence of unmet need forfamily planning. Objective: To determine the relationship between wife’sknowledge and husband’s support toward  the incidence of unmet need forfamily planning. Method: This research was an analytic study with crosssectionalapproach conducted from April to June 2014. As much as 96reproductive couple were included in this study. Data was analyzed usingChi-Square test. Result: There were relationship between wife’sknowledge and husband’s support toward the incidence of unmet need forfamily planning with p=0,000 and p=0,000, rescpectively. Conclusion:wife’s knowledge and husband’s support are related to unmet need forfamily planning.Keywords: unmet need for family planning, wife’s knowledge, husband’ssupport. 1. Medical School, Faculty of Medicine, Universitas Tanjungpura,Pontianak, West Kalimantan. 2. Departement of Public Health, Faculty of Medicine, UniversitasTanjungpura Pontianak, West Kalimantan. 3. Departement of Physiology, Faculty of Medicine, UniversitasTanjungpura, Pontianak, West Kalimantan.